A comparative study of coal mine safety performance indicators in China and the USA. (29th December 2014) - Nieto, A.; Gao, Y.; Grayson, L.; Fu, Gui
Safety performance indicators are the basis for effective accident statistics, playing a crucial role in accident analysis and prevention. To better understand China's safety performance indicators system, a comparative analysis of the coal mine safety performance indicators used in China and USA is introduced. The number of fatalities, the number of accidents and the fatality rate per million tons are usually used as the safety performance indicators by the Chinese government in the coal mining industry, whereas in the USA, the number of fatalities, the number of reportable injuries, the associated incidence rates, the number of lost work days and the severity measure are widely used for measuring accidents and injuries and the number of citations, S&S designated citations and orders are primarily used for measuring violations. On the basis of this comparative analysis, this paper proposes to establish the reportable injuries standard, the lost work days statistics standard and the unified violations standard in China.